MULTIMOORA strategy for solving multi‐attribute group decision making (MAGDM) in trapezoidal neutrosophic number environment. Issue 3 (23rd June 2020) - Pramanik, Surapati; Mallick, Rama
Abstract : The main purpose of this study is to bring in a new extension of multi‐objective optimisation on the basis of ratio analysis plus full multiplicative form (MULTIMOORA) in trapezoidal neutrosophic number (TrNN) environment. MULTIMOORA strategy provides high efficiency and effectiveness in problem‐solving. The new MULTIMOORA strategy consists of three components. The components are ratio system approach, reference point approach, and full multiplicative form. To develop the proposed strategy, the authors find out three ranking order of alternatives using the three components. The final ranking order of the alternatives is based on dominance property. The study is original as it first develops the MULTIMOORA strategy in the TrNN environment, which they call TrNN‐ MULTIMOORA. They solve a realistic banking problem involving multi‐attribute group decision making in the TrNN environment to reflect the applicability and proficiency of the developed strategy. They also present a comparison between the proposed strategy and the existing tomada de decisao interativa e multicritévio and VlseKriterijumska Optimizcija I Kaompromisno Resenje strategies.